The Ability of Students in Aplicating Tajwid While Reading the Holy Quran - Nisa Nurzanah; Chaerul Rochman; Maslani (Tarbiyah Departement collaboration with AMCA, 2019)
We as Muslims are inseparable from learning the Holy Qur'an, because the Qur'an is the source and basis of the first and foremost law. Therefore studying the Qur'an from various scientific aspects is very important. To get the knowledge in depth and in detail in terms of reading it requires mastery and application of recitation. Reading the Qur'an with its legal recitation is fard ain for every Muslim. This research was carried out to see how the students' ability to apply Tajweed in reading Al-Qur'an letter Al-Maidah verse 48. The author took basic competencies in reading Q.S Al-Maidah / 5: 48 according to the rules of recitation and makhrajul letters. This research was obtained by conducting tests on 30 students of class XI in Budi Luhur Cimahi High School. After the results are known, the authors conducted interviews with several students who were still lacking in applying the rules of recitation and pronunciation of makhrajul letters. This is because students rarely read the Koran and have never studied tajwid.